Strategi Guru dalam Meningkatkan Minat Baca Siswa di MI Yaqin 3 Kwang Rundun Desa Kwang Rundun Kecamatan Jerowaru: Teachers' Strategies in Increasing Students' Reading Interest at MI Yaqin 3 Kwang Rundun, Kwang Rundun Village, Jerowaru District - Ittihad; Yuni Wardatussururi (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2025)
Indonesians' interest in and habit of reading is still relatively low. One reason is the cultural transition from oral to written language, which has not yet been fully and evenly realized. This study aims to describe the strategies used by Indonesian language teachers to increase the reading interest of fourth-grade students at MI Yaqin 3 Kwang Rundun, Kwang Rundun Village, Jerowaru District. The background of this study is the low interest in reading among students which impacts their ability to understand texts and their achievement in learning Indonesian. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews, and documentation. The results show that teachers apply various strategies such as the use of illustrated story media, class reading corners, giving interesting reading assignments, and literacy project-based learning. These strategies have proven effective in increasing student participation in reading activities, building daily reading habits, and fostering interest in reading. This study concludes that creative and contextual teacher strategies can be an important factor in building a culture of literacy in elementary schools.